Implementation of the Deep Learning Approach in Elementary School Mathematics Learning - Sandi Budi Iriawan; Tatat Hartati; Babang Robandi (AL-ISHLAH: Jurnal Pendidikan, 2025)
Challenges such as limited facilities, insufficient professional training, and resistance to pedagogical innovation hinder the effective implementation of advanced learning approaches in elementary education. This study aims to analyze how the deep learning approach is implemented in mathematics instruction at the elementary school level. A qualitative research design with a case study method was employed. Participants included 29 elementary school teachers—9 from Pagerwangi I Public Elementary School and 20 from Madrasah Ibtidaiyyah Al-Haq, West Java—selected through purposive sampling. Data were collected using an observation instrument designed to assess the implementation of deep learning practices. Data analysis followed the Miles and Huberman model, involving data reduction, presentation, and conclusion drawing. The findings show that the average teacher competency score in implementing the deep learning approach was 78.06%, categorized as "good." The implementation was structured around three key stages: initial, core, and closing activities. Initial activities focused on student readiness, motivation, and contextual connections. Core activities emphasized conceptual understanding, application, and the development of higher-order thinking skills. Closing activities involved reflection, feedback, assessment, and planning for subsequent learning. The study concludes that teachers demonstrated a solid alignment between deep learning principles and instructional practice. However, achieving optimal implementation requires further development of teachers’ conceptual understanding and emotional and social readiness. Enhancing these areas is essential for sustaining meaningful, mindful, and joyful learning experiences in mathematics education at the elementary level. Future professional development programs should address these dimensions to support continued pedagogical transformation.